Case Report: Severe Gonadal Dysgenesis Causing 46,XY Disorder of Sex Development Due to a Novel NR5A1 Variant - Alhamoudi, Kheloud M.; Alghamdi, Balgees; Aljomaiah, Abeer; Alswailem, Meshael; Al-Hindi, Hindi; Alzahrani, Ali S. (Frontiers in Genetics, 2022)
Mutations in the nuclear receptor subfamily 5 group A member 1 (NR5A1) are the underlying cause of 10-20% of 46,XY disorders of sex development (DSD). We describe a young girl with 46,XY DSD due to a unique novel mutation of the NR5A1 gene. An 11-year old subject, raised as a female, was noticed to have clitromegly. She looked otherwise normal. However, her evaluation revealed a 46,XY karyotype, moderate clitromegly but otherwise normal female external genitalia, undescended atrophied testes, rudimentary uterus, no ovaries and lack of breast development. Serum testosterone and estradiol were low and gonadotropins were elevated. Adrenocortical function was normal. DNA was isolated from the peripheral leucocytes and used for whole exome sequencing. The results were confirmed by Sanger sequencing. We identified a novel mutation in NR5A1 changing the second nucleotide of the translation initiation codon (ATG>ACG) and resulting in a change of the first amino acid, methionine to threonine (p.Met1The). This led to severe gonadal dysgenesis with deficiency of testosterone and anti mullerian hormone (AMH) secretion. Lack of the former led to development of female external genitalia and lack of the latter allowed mullerian duct to develop into uterus and upper vagina. The patient has a female gender identity. Bilateral orchidectomy was performed and showed severely atrophic testes. Estrogen/progesterone therapy was initiated with excellent breast development and normal cyclical menses. We described a severely affected case of 46,XY DSD due to a novel NR5A1 mutation involving the initiation codon that fully explains the clinical phenotype in this subject.